PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Desy Wulansari; Prihantoro Prihantoro (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Banking plays an important role as an intermideary function and it makes the economic entrepreneurs have an active role in investing like capital market. The rapid competition in the banking world industry encourages investors to make decision carefully. One of company internal information which is needed by the investor is financial report about financial performance such as LDR, ROA, NIM, and BOPO. The data used in this research is quarterly secondary data for 2007- 2009. By using fundamental analysis at least it helps the investors to select investment based on 160 samples tested from 16 banks in 2007-2009. It is found 2 variables which affect toward partal stock rate named ROE and NIM, meanwhile simultaneous testing LDR, ROA, ROE, NIM, and BOPO effect s significantly toward the stock price for 59,4 %, while for 40,6% is effected by other variables. The relation influence of LDR and BOPO is negative, meanwhile ROA, ROE, and NIM give positive effect toward stock price.